Effects of rhamnolipids on growth performance and intestinal health parameters in Linnan yellow broilers - Bing Zhang; Guangyong Chen; Haoran Zhang; Junhong Lan; Caimei Yang (Poultry Science, 2021)
This study determined the effects of dietary supplementation of rhamnolipids (RLS) on the growth performance, gut morphology, immune function, intestinal volatile fatty acid, and microflora community in Linnan yellow broilers. A total of 480 1-day-old broiler chicks were randomly assigned to groups for supplementation with one of the following for 56 d: no supplement (control), 30 mg/kg bacitracin (ANT), 500 mg/kg RLS, or 1,000 mg/kg RLS (RLS2). The RLS2 diet was found to improve the final BW and ADG on day 56. The RLS diet reduced jejunal crypt depth, increased jejunal villus length, and increased serum IgA, IgM, IgY, IL-1β, IL-6, and tumor necrosis factor-alpha (TNF-α) levels. The RLS broilers had higher cecum concentrations of acetic acid, propionic acid, butyrate, isobutyric acid, valerate, and isovalerate. High-throughput sequencing indicated that RLS affected microbial quantity and diversity in the cecum. Bacterial richness was higher in the RLS broilers than the ANT broilers. The RLS broilers had higher relative abundances of Megasphaera hypermegale and Lachnospiraceae bacterium 19gly4 on day 28 and Clostridium spiroforme and Alistipes obesi on day 56. These results suggest that RLS supplementation improves growth performance, benefits the intestinal villus morphology, regulates host immune function, and raises intestinal volatile fatty acid content and the relative abundance of the gut microbiota in broiler chickens.